The emerging role of immunotherapy in gastric and esophageal adenocarcinoma. (August 2016) - Bockorny, Bruno; Pectasides, Eirini
Gastric and esophageal adenocarcinomas are aggressive malignancies. Systemic therapy for these tumors relies primarily on cytotoxic chemotherapy but outcomes remain poor. In recent years, immunotherapy has emerged as a new, promising therapeutic approach for a variety of solid tumors. Characterization of gastroesophageal cancers has revealed genomic and immune features of these tumors that may predict response to immunotherapy. Indeed, preliminary results from the initial trials of immune checkpoint inhibitors have been encouraging, with objective response rates of 20% in heavily pretreated patient populations. Based on these results, additional trials of single-agent checkpoint inhibitors as well as combinations with chemotherapy and targeted therapies are currently ongoing. Further work to identify predictive biomarkers will be crucial for the successful implementation of immunotherapy.